Natural versus commercial carbohydrate supplementation and endurance running performance - Too, B. W.; Cicai, S.; Hockett, K. R.; Applegate, E.; Davis, B. A.; Casazza, G. A. (Journal of the International Society of Sports Nutrition, 2012)
We examined the metabolic, performance and gastrointestinal (GI) effects of supplementation with a natural food product (raisins) compared to a commercial product (sport chews). Methods: Eleven male (29.3 +/- 7.9 yrs; mean and SD) runners completed 3 randomized trials (raisins, chews and water only) separated by 7 days. Each trial consisted of 80-min (75%VO2max) treadmill running followed by a 5-km time trial (TT). Heart rate (HR), respiratory exchange ratio (RER), blood lactate, serum free fatty acids (FFA), glycerol and insulin, plasma glucose, electrolytes and creatine kinase, GI symptoms and rating of perceived exertion (RPE) were recorded every 20-min. We employed a within-subject two-way analysis of variance (ANOVA) for repeated measures with a Fisher's post hoc analysis to determine significant differences. Results: VO2, HR, electrolytes, lactate, glycerol and RPE did not differ due to treatment. Average plasma glucose was maintained at resting levels (5.3 +/- 0.4 mmol * L-1) during the sub-maximal exercise bout (5.9 +/- 0.6, 5.7 +/- 0.6 and 5.5 +/- 0.5 mmol * L-1 for chews, raisins and water respectively), and was significantly higher with chews than water only. RER and % of non-protein macronutrient oxidation derived from carbohydrate was highest with chews, followed by raisins and water was the lowest (74.4 +/- 6.4, 70.0 +/- 7.0 and 65.1 +/- 8.7 % for chews, raisins and water respectively) during the sub-maximal exercise period. Serum FFA was higher in the water treatment versus both raisins and chews at 80 min of sub-maximal exercise. Serum insulin was higher with the chews than both raisins and water (5.1 +/- 2.0, 3.1 +/- 0.8, 1.9 +/- 0.6 uU * ml-1 for chews, raisins and water respectively). Plasma creatine kinase, corrected for baseline values, for the last 40 min of the sub-maximal exercise bout, was higher with raisins compared to other treatments. The TT was faster for both carbohydrate treatments (20.6 +/- 2.6, 20.7 +/- 2.5, 21.6 +/- 2.7 min for raisin, chews and water respectively). GI disturbance was mild for all treatments. Conclusion: Raisins and chews promoted higher carbohydrate oxidation and improved running performance compared to water only. Running performance was similar between the raisins and chews, with no significant GI differences.